Renaissance themes : essays presented to Arun Kumar Das Gupta - Chaudhuri, Sukanta, 1950-; Das Gupta, Arun Kumar (Anthem Press, 2009)
These essays present a view of English literature and drama in a context of humane literary studies: a critical ambience harking back to the Renaissance.